Effect of insect pollinators on quantitative yield parameters of okra (Abelmoschus esculentus) in mid-Himalayan region - SUBBANNA, A R N S; PASCHAPUR, AMIT UMESH; BHAT, SUNAULLAH; CHAUDHARI, GANESH; DEV, RAHUL; HEDAU, NIRMAL KUMAR; MISHRA, K K; KANT, LAKSHMI (The Indian Journal of Agricultural Sciences, 2024)
Okra [Abelmoschus esculentus (L.) Moench] is an often cross-pollinated crop with up to 19–42% of cross pollination assisted by insects and planned pollination may improve the economic fruit yield and biological parameters. The present study was carried out during rainy (kharif) seasons of 2021 and 2022 at Research Farm of ICAR-Vivekananda Parvatiya Krishi Anusandhan Sansthan, Hawalbagh, Almora, Uttarakhand to assess the pollinator diversity and possible results (both biological and economical) of planned bee pollination. The study on floral visitors of okra recorded 28 insect spp. belonging to four insect orders, among which five spp., viz. Apis cerana indica (Fabricius) 1798, Apis mellifera (Linnaeus) 1758, Bombus haemorrhoidalis (Smith) 1852, Lithurgus atratus (Smith) 1853 and Xylocopa latipes (Drury) 1773 were predominant. The foraging activity and pollination behaviour showed that two non-Apis bee species (X. latipes and B. haemorrhoidalis) were swift flyers and visited more numbers of flowers per unit time. It was noticed that, peak period of pollinator’s visitation was between 9.00–11.00 h accounting to 113.76±7.65 insects/m2/10 min, during which stigma receptivity and pollen germination were at its peak. Assessment of yield related parameters of insect pollinated flowers showed superior quality fruits with better capsule length (17.4–20.9 cm), capsule girth (6.56–7.84 cm), seeds/capsule (51.4–60.6), test weight of 100-seeds (7.05–8.38 g) and even the seed yield (1.86–3.04 tonnes/hectare) than closed control and hand pollination (emasculated and cross pollinated). In conclusion, ecological engineering of okra fields enhances the pollination rate and ultimately the yield and seed quality.